2020
DOI: 10.1177/1359104520925526
|View full text |Cite
|
Sign up to set email alerts
|

Caring for gender diverse children and adolescents in Italy: A mixed-method investigation of clinicians’ knowledge and approach to clinical practice

Abstract: Introduction: In today’s Italy, gender diversity has assumed a remarkable resonance and visibility in both scientific and popular literature, which has facilitated the development of studies regarding treatments and support for children and adolescents with gender-related issues. Aim: the aim of this study was to conduct a preliminary evaluation of how Italian clinicians (psychologists and pediatricians) perceive gender variant children and adolescents, evaluating their approach to clinical practice. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 60 publications
(70 reference statements)
2
8
0
Order By: Relevance
“…In some cases, the agencies' psychological work with parents focused on helping them to elaborate the loss of their child's natal gender (and usually the anticipation of becoming a grandparent). Consistent with the literature [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78], mothers tended to appear less frightened than fathers, and both parents were reported to have concerns related to a lack of knowledge on how to act: "They [mother and father] usually disagree on everything. Mothers tend to blame themselves, judging themselves as having been too cold or too suffocating .…”
Section: Psychological Support (For Youths and Families)supporting
confidence: 76%
See 1 more Smart Citation
“…In some cases, the agencies' psychological work with parents focused on helping them to elaborate the loss of their child's natal gender (and usually the anticipation of becoming a grandparent). Consistent with the literature [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78], mothers tended to appear less frightened than fathers, and both parents were reported to have concerns related to a lack of knowledge on how to act: "They [mother and father] usually disagree on everything. Mothers tend to blame themselves, judging themselves as having been too cold or too suffocating .…”
Section: Psychological Support (For Youths and Families)supporting
confidence: 76%
“…Within this context, the work of clinicians in the specialized centers has remained understudied. While previous Italian qualitative studies have investigated the experiences of trans * individuals [61,62], their families [63], and clinicians working outside of specialized services [64], to the best of our knowledge, the present study was the first to investigate the perspectives of clinicians and volunteers within specialized centers and associations for trans * youths, with respect to agency functioning and shortcomings.…”
Section: Introductionmentioning
confidence: 98%
“…Some of these may be particularly pertinent to younger people. In addition, the acceptance of family members and the knowledge of healthcare providers are crucial in young people’s healthcare navigation 11 12…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, research (Vocks et al, 2009;Couturier et al, 2015;Witcomb et al, 2015;Becker et al, 2016;Jones et al, 2016;Mirabella et al, 2020) has reported that BD in individuals with GD extends beyond non-sexual body parts and, therefore, represents a significant source of suffering. Moreover, many studies have noted that the distress associated with BD may be increased in transgender people, due to discrimination and stigma in their life contexts (e.g., Clements-Nolle et al, 2006;Ristori and Steensma, 2016;Giovanardi et al, 2018Giovanardi et al, , 2020aFortunato et al, 2020).…”
Section: Introductionmentioning
confidence: 99%